LITERASI ASESMEN MAHASISWA CALON GURU PADA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS KHAIRUN TERNATE - Ridwan Jusuf; Dharmawaty Hadi; Nurmaya Papuangan (EDUKASI, 2022)
This study aims to determine the literacy level of the assessment of prospective teachers at the Faculty of Teacher Training and Education Unkhair. Respondents in this study were 3rd, 5th, and 7th semester students spread over 10 FKIP study programs, respondents were asked to fill out an assessment literacy test instrument which was developed based on the Assessment Literacy Standard. There are seven assessment literacy standards that can be used to measure the assessment literacy of prospective teachers, including: choosing assessment methods, developing assessment methods, managing and interpreting assessment results, using assessment results, developing assessment procedures, communicating assessment results and recognizing unethical assessment methods, illegal, and inappropriate. The instrument was given to respondents through the googleform application. The collected data was then analyzed with descriptive statistics. The results of this research analysis can reveal the level of literacy skills in the assessment of prospective teachers in 10 study programs as follows: Indonesian Language and Literature Education 73% high category, English Language Education 72% high category, Pancasila and Citizenship education 74% high category, Geography Education 75% category High category, Chemistry Education 77% high category, Physics Education 78% high category, Biology Education 78% high category, Early Childhood Education 76% high category and Elementary School Teacher Education 78% high category. Based on the results of the data analysis, it can be concluded that the average assessment literacy ability for prospective teachers in FKIP is in the high category, this happens because the content of the learning evaluation courses in each FKIP study program has given a good understanding to prospective teacher students as a provision for later becoming teachers who are professional in assessing and evaluating students in schools.